Writing a book (Journal of Parents and Teachers, 2026)
Carlos and Gonzalo, primary school teachers, wrote the book Un oficio sin paredes (A Profession Without Walls), reflecting on teaching and learning. Joaquín María García de Dios praises their initiative and highlights the importance of educators improving their profession from within, seeking quality and recognition through the creative growth of their students.
Keywords: Education; Discovery; Creativity; Recycling